Analisis Perdagangan Internasional Indonesia pada Kebijakan ACFTA dan AKFTA - Riady Ibnu Khaldun (Jurnal Simki Economic, 2024)
Current international trade policies open up opportunities to minimize various forms of obstacles, so that every party that agrees on these policies feels the convenience of the transaction process. These efforts are in line with what is stated in trade liberalization, namely reducing restrictions on trade, both in the form of tariff and non-tariff policies. Among several free international trade policies that have been ratified by Indonesia, there are two policies that have the potential to be optimized in order to get maximum benefits, namely the ASEAN China Free Trade Area (ACFTA) and the ASEAN Korea Free Trade Area (AKFTA). The purpose of this research is to analyze international trade on ACFTA and AKFTA policies. Where this study uses a qualitative research design with a descriptive approach method and the data used in this study are secondary data derived from previous research, publications originating from various government agencies both offline and online, as well as other supporting documents. The results of this study indicate that the ACFTA free trade policy was signed on November 4 2002 and its implementation began in January 2010 on the AKFTA was signed on August 24 2006, between the two free trade agreements each emphasizing the elimination of tariffs for 80% of goods traded. traded, protecting market access and ensuring a more transparent environment for investors for AKFTA, as well as the elimination of tariffs for 94.6% of all tariff lines for exports from Indonesia to China.